2018
DOI: 10.1002/adfm.201707161
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Paper–Plastic Microchip for Flexible and High‐Performance Point‐of‐Care Diagnostics

Abstract: A low-cost and easy-to-fabricate microchip remains a key challenge for the development of true point-of-care (POC) diagnostics. Cellulose paper and plastic are thin, light, flexible, and abundant raw materials, which make them excellent substrates for mass production of POC devices. Herein, a hybrid paper–plastic microchip (PPMC) is developed, which can be used for both single and multiplexed detection of different targets, providing flexibility in the design and fabrication of the microchip. The developed PPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 46 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Since firstly introduced by Whitesides et al in 2007, μ PADs have enjoyed booming development for POC diagnostic applications due to their inherent advantages provided by the paper-based substrates, such as hydrophilic and porous structure for microfluidic channels fabrication, low cost, fold ability, disposability, favorable biocompatibility, no need of external driven force for sample transportation, and equipment independence [380] , [381] , [382] , [383] , [384] , [385] , [386] . Typical μ PADs were composed of an arrangement of hydrophilic/hydrophobic microstructures patterned on paper substrates that integrated reagent storage, sample transportation, sorting, mixing, flow control and multiplex detection, making them ideal alternatives for automated field testing and POC diagnostic applications [385] , [386] , [387] .…”
Section: Poc Devices For Infectious Disease Detectionmentioning
confidence: 99%
“…Since firstly introduced by Whitesides et al in 2007, μ PADs have enjoyed booming development for POC diagnostic applications due to their inherent advantages provided by the paper-based substrates, such as hydrophilic and porous structure for microfluidic channels fabrication, low cost, fold ability, disposability, favorable biocompatibility, no need of external driven force for sample transportation, and equipment independence [380] , [381] , [382] , [383] , [384] , [385] , [386] . Typical μ PADs were composed of an arrangement of hydrophilic/hydrophobic microstructures patterned on paper substrates that integrated reagent storage, sample transportation, sorting, mixing, flow control and multiplex detection, making them ideal alternatives for automated field testing and POC diagnostic applications [385] , [386] , [387] .…”
Section: Poc Devices For Infectious Disease Detectionmentioning
confidence: 99%
“…Therefore, paperbased devices provide attractive alternative to traditional labbased assays and allows affordable and rapid disease testing [70]. Recently, paper-based microfluidic devices are being investigated for ZIKV detection [73,74]. At one instance, paper-based device consists of a large area at the top for sample loading (blood or plasma) followed by several areas coated with specific antibodies against ZIKV's NS1 protein [73].…”
Section: Recent Development In Zika Virus Testing and Diagnosticsmentioning
confidence: 99%
“…Microfluidic devices provide a precise control on fluid flow and are widely investigated for various applications including disease detection [87][88][89][90][91], sample analysis [88], and biosensing [92][93][94][95]. The previous studies have shown that microfluidic devices can be used for the quantification of various viruses [69,74] and proteins through impedance sensing [96,97]. Recently, newly designed biochips integrating with electrical detection electrodes have been optimized by the addition of pillar structures, which serve to facilitate the functionalization of probes inside the chip, thus increasing the hit rate of target proteins [98].…”
Section: Reverse Transcription Loop Mediated Isothermal Amplificationmentioning
confidence: 99%
See 2 more Smart Citations